Uma nova polícia, um novo policial: uma biografia intelectual do coronel Carlos Magno Nazareth Cerqueira e as políticas de policiamento ostensivo na redemocratização fluminense (1983-1995) - Silva, Bruno Marques (2016)
The thesis intends to carry out a biographical analysis of Colonel PM Carlos Magno Nazareth Cerqueira, with a professional and intellectual profile. His name represented one of the most important intellectual expressions of a group of officers 'reformist' engaged in reforms in the Military Police of Rio de Janeiro State (PMERJ) in government of Leonel Brizola (1983-95). Attentive to the new international policing strategies, these new managers, led by Nazareth Cerqueira, redefined the role of the corporation from concepts such as prevention, community integration and legality, facing the military police as a 'public service'. The general commander of PMERJ tried to build a new regulatory framework in the administration of public security in the state of Rio de Janeiro and in particular the ostensible police work. Cerqueira, to seek the adequacy of police activity and objectives of communities, fought the traditional social control policies, providing concrete institutional contours to the brizolista human rights speech. The biggest challenge of this policy work was to disciplinary the policy themselves on a new basis. His command, when testing the Community model of policing in Rio de Janeiro, constituted an important contribution of pedetistas governments for Brazilian democracy in the 1980s and 90s. Colonel Cerqueira’s ideas and projects are fundamental to understand the continuities and changes in the treatment of public safety. The concepts and methods offered by Political History and the Intellectual History were used to recover his significant contribution in the field of ideas and political disputes.